Structural basis for the synthesis of the core 1 structure by C1GalT1 - González-Ramírez, Andrés Manuel (2022)
LA/P/0140/2020 MX20229-11 BFU2016-75633-P PID2019-105451GB-I00 RTI2018-099592-B-C21 E34_R17 LMP58_18 DNRF107 LA/P/0140/2020 2020.00233.CEECIND 2020.03261.CEECIND ROTEIRO/0031/2013–PINFRA/22161/2016 N°283570 BIOSTRUCTX_5186). Publisher Copyright: © 2022, The Author(s).